FACTORS AFFECTING STUDENTS’ IN SPEAKING PERFORMANCE AT SMPN 1 IV JURAI - Rahmandalil Permanda; Sefrinal Sefrinal; Veni Veni; Riski Safitri; Syamsuardi Syamsuardi; Dino Adi Putra (STKIP Pesisir Selatan, 2023)
Speaking is one of the components in learning english, and also speaking is one of the skills that must be mastered by students. However, in reality there are still many students who have problems with their speaking appearance when they perform in front of the classat SMPN 1 IV JURAI. This study aims to find out what factors affect the speaking performance of students at SMPN 1 IV JURAI when appearing in front of the class. This type of research is descriptive research. Participation in this study was 81 grade VII students. The technique used in sampling in this study was total sampling, namely all grade VII students at SMPN 1 IV JURAI. In this study researcher used quetionnaire and interviews as instruments and data processing technique consiting of 35 qustionnaire questions and 6 qustions from interviews that have been explained by several experts. Based on the results of data analysis obtained showsthat this study found these 5 factors with different percentages,namely: Performance Condition 40,22%, Affective Factors 18.11%, Listening Ability 3.1%, Topical Knowledge 2.15%, and Feedback During Speaking Ability 2.71%. Based on the results of these percentage, it is obtained that all these factors can affect the appearance of students’ when speaking performance in front of the class.